2008
DOI: 10.1111/j.1540-8159.2008.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular Pacing Attenuates T‐Wave Alternans and T‐Wave Amplitude Compared to Other Pacing Modes

Abstract: BV pacing attenuates TWA in tandem with reduced T-wave magnitude. In these patients with baseline QRS prolongation, RV-TWA predicted events more effectively than BV-TWA and RA-TWA. Further studies are required to understand how altered ventricular activation influences repolarization dynamics and arrhythmic tendency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Two previous studies compared the effects of different pacing modes on the incidence of TWA in patients with low LV function, and Ehrlich, et al found a high level of concordance between TWA test results obtained during RAP and results obtained under other pacing modes; they also reported that TWA assessment seems not to be influenced by BVP in congestive heart failure patients 16) . Anh, et al reported that BVP attenuates TWA in tandem with reduced T-wave magnitude and that, in patients with baseline QRS prolongation, TWA during RVP predicts events more effectively than does BVP or RAP 15) . Results of the present study were not concordant with results of these previously reported studies 15,16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies compared the effects of different pacing modes on the incidence of TWA in patients with low LV function, and Ehrlich, et al found a high level of concordance between TWA test results obtained during RAP and results obtained under other pacing modes; they also reported that TWA assessment seems not to be influenced by BVP in congestive heart failure patients 16) . Anh, et al reported that BVP attenuates TWA in tandem with reduced T-wave magnitude and that, in patients with baseline QRS prolongation, TWA during RVP predicts events more effectively than does BVP or RAP 15) . Results of the present study were not concordant with results of these previously reported studies 15,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Anh, et al reported that BVP attenuates TWA in tandem with reduced T-wave magnitude and that, in patients with baseline QRS prolongation, TWA during RVP predicts events more effectively than does BVP or RAP 15) . Results of the present study were not concordant with results of these previously reported studies 15,16) . The reason for the discrepancy is unclear; however it is possible that underlying heart disease, heart failure status, and/or timing of the TWA measurement after implantation of the CRT device influenced the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous investigations into this relationship in humans with heart failure have been inconsistent (1,7). Thus, further research is needed to elucidate the relationship between TWA and other indexes of repolarizaiton, including the T-wave amplitude and area.…”
Section: Min (Peak Effect) After the Injection Of Isoproterenolmentioning
confidence: 93%
“…Recent studies (1,5) in humans with heart failure have shown that changes in the T wave amplitude and area could be related to alterations in the repolarization sequence. Thus, the changes in the T wave amplitude and area observed in FVB mice could also be related to the alterations of the repolarization sequence induced by adrenergic stimulation and associated changes in CLs.…”
Section: Min (Peak Effect) After the Injection Of Isoproterenolmentioning
confidence: 98%